Hormonal contraceptive phases matter: Resting-state functional connectivity of emotion-processing regions under stress - Padideh Nasseri (Neurobiology of Stress, 2020)
Hormonal contraceptives (HCs) affect various processes related to emotion processing, including emotional memory, fear extinction, and the cortisol response to stress. Despite the modulating role of HCs on the stress response in women and variance in synthetic hormone levels across the HC cycle, little is known about the phase-related effects of HCs on the brain's response to stress. We investigated the effect of HC cycle phase on functional connectivity of memory- and emotion-related regions at rest after exposure to a stressor. Twenty HC users completed two sessions of resting-state functional magnetic resonance imaging after exposure to the cold pressor test, one during the hormone-present HC phase (when synthetic hormones are taken) and one during the hormone-absent HC phase (when synthetic hormones are not taken). Women showed higher functional connectivity between left amygdala and ventromedial prefrontal cortex during the hormone-present phase. During the hormone-absent phase, women showed higher coupling between left parahippocampus and right superior lateral occipital cortex. Our results suggest that the synthetic hormones contained in HCs may protect against the negative effects of stress on functional connectivity of emotional processing regions.